(untitled) (Revista Innova Educación, 2022)
The objective of this work was to integrate a Hybrid Model of Regional Educational Identity for marginalized areas of the Otomí Tepehua region, in the east of the state of Hidalgo, Mexico, whose purpose is to reinforce distance education for areas with a high degree of vulnerability. It was a qualitative, descriptive, non-experimental, cross-sectional and in situ investigation based on theoretical references through grounded theory, the data collection technique was semi-structured in-depth interviews. The result was to integrate the endogenous and exogenous forces from the data obtained from the context in a model with each of its variables and the requirements for its implementation, it was concluded in a reflection of the attempts that governments of all levels and of Theoreticians have presented given the COVID-19 scenario, in the urgent need for adequate connectivity in the study area and in the need to consider holistic, flexible, regional and global learning, and include concepts that come from its uses, customs and form. of life integrated into an international reality.